Partial Purification and Biochemical Evaluation of Protease Fraction (MA-1) from Mycoleptodonoides aitchisonii and Its Fibrinolytic Effect - Sung-Ho Lee; Seung-Yub Song; Jun-Hui Choi; Seung Kim; Hyo-Jeong Lee; Jin Woo Park; Dae-Hun Park; Chun-Sik Bae; Seung-Sik Cho (MDPI AG, 2023)
The antioxidative proteolytic fraction, MA-1, was partially purified from Mycoleptodonoides aitchisonii. MA-1 was purified to homogeneity using a two-step procedure, which resulted in an 89-fold increase in specific activity and 42.5% recovery. SDS-PAGE revealed two proteins with a molecular weight of 48 kDa. The zymography results revealed proteolytic activity based on the MA-1 band. MA-1 was found to be stable in the presence of Na+, Ca2+, Fe3+, K+, and Mg2+. MA-1 was also stable in methanol, ethanol, and acetone, and its enzyme activity increased by 15% in SDS. MA-1 was inhibited by ethylenediaminetetra-acetic acid or ethylene glycol tetraacetic acid and exerted the highest specificity for the substrate, MeO-Suc-Arg-Pro-Tyr-pNA, for chymotrypsin. Accordingly, MA-1 belongs to the family of chymotrypsin-like metalloproteins. The optimum temperature was 40 °C and stability was stable in the range of 20 to 35 °C. The optimum pH and stability were pH 5.5 and pH 4-11. MA-1 exhibited stronger fibrinolytic activity than plasmin. MA-1 hydrolyzed the Aα, Bβ, and γ chains of fibrinogen within 2 h. MA-1 exhibited an antithrombotic effect in animal models. MA-1 was devoid of hemorrhagic activity at a dose of 80,000 U/kg. Overall, our results show that M. aitchisonii produces an acid-tolerant and antioxidative chymotrypsin-like fibrinolytic enzyme, and M. aitchisonii containing MA-1 could be a beneficial functional material for the prevention of cardiovascular diseases and possible complications.